2014
DOI: 10.1016/j.ijrobp.2014.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Spectroscopic Imaging of Glioblastoma Multiforme Radiation Treatment Volumes

Abstract: Purpose Magnetic resonance (MR) imaging and computed tomography (CT) are used almost exclusively in radiation therapy planning of glioblastoma multiforme (GBM), despite their well-recognized limitations. MR spectroscopic imaging (MRSI) can identify biochemical patterns associated with normal brain and tumor, predominantly by observation of choline (Cho) and N-acetylaspartate (NAA) distributions. In this study, volumetric 3-dimensional MRSI was used to map these compounds over a wide region of the brain and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 26 publications
2
41
1
Order By: Relevance
“…From a larger study of 56 treatment-naĂŻve patients with histopathology-confirmed glioma, 20 were grade IV (8, 21). The institutional ethics committee and the research committee Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India approved the study protocol, and informed consent was obtained from the patients or their care providers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…From a larger study of 56 treatment-naĂŻve patients with histopathology-confirmed glioma, 20 were grade IV (8, 21). The institutional ethics committee and the research committee Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India approved the study protocol, and informed consent was obtained from the patients or their care providers.…”
Section: Methodsmentioning
confidence: 99%
“…The institutional ethics committee and the research committee Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, India approved the study protocol, and informed consent was obtained from the patients or their care providers. In a prior study, 1 patient was removed because of lack of T2w/FLAIR sequence (8); 2 more patients were removed for this work because they did not have CE-T1w imaging. Thus in this report the remaining 17 patients were analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same group showed that this additional metabolic information would not only change the size but also would result in a substantial shift of the volumes if considered for radiation target delineation. 76 By this means, Parra et al 77 compared metabolic tumour volumes with standard RT volumes using an advanced volumetric three-dimensional (3D) MRSI approach and found in an observational study of n 5 19 patients with GBM that on average, one-third Cho-defined volume was not covered by the CTV receiving 60 Gy. Park et al 78 studied the CNI2 volume at therapy initiation in another observational study of n 5 23 patients with GBM and showed that one-third of recurrent-enhancing GBM volume within this metabolically active tumour region was not initially covered by the 60-Gy RT target.…”
Section: Imaging Implications In Neurosurgerymentioning
confidence: 99%